PENGARUH LABA AKUNTANSI, ARUS KAS OPERASI DAN UKURAN PERUSAHAAN TERHADAP DIVIDEN KAS PADA PERUSAHAAN JASA KEUANGAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2018-2022 - Surya Putri, Fidela Lathifah; Piliang, Arfah; Masril, Masril; Menhard, Menhard (Komunitas Manajemen Kompetitif, 2025)
The aim of the research is to determine the effect of accounting profit, operating cash flow and company size on cash dividend in banking financial services companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The population in this study were 47 banking financial services companies listed on the Indonesia Stock Exchange and only 8 companies met the criteria to be the research sample. This research uses a quantitative approach and the sampling technique uses a purposive sampling method. The data analysis technique used is multiple linear regression analysis. The results of this research show that: accounting profit and operating cash flow partially influence cash dividend. Company size has no partial effect on cash dividend. Accounting profit, operating cash flow and company size simultaneously influence cash dividend.